2015
DOI: 10.3332/ecancer.2015.507
|View full text |Cite
|
Sign up to set email alerts
|

Fertility sparing treatment in borderline ovarian tumours

Abstract: Borderline ovarian tumours are low malignant potential tumours. They represent 10–15% of all epithelial ovarian malignancies. Patients with this type of tumour are younger at the time of diagnosis than patients with invasive ovarian cancer. Most of them are diagnosed in the early stages and have an excellent prognosis. It has been quite clearly established that the majority of borderline ovarian tumours should be managed with surgery alone. Because a high proportion of women with this malignancy are young and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 89 publications
2
16
0
Order By: Relevance
“…There was no significant difference in PFS between the other methods of fertility-preserving surgery (USO and USO + CC) and radical surgery, or among the three styles of fertility-preserving surgery. This is corroborated by findings in other studies: Chen et al found that the choice of surgical methods used to preserve fertility had significant impact on recurrence and subsequent pregnancy [15]; the same is reported in other studies [16, 17]. Taken together, these results suggest that the types of fertility-preserving surgery have different impacts on oncologic and pregnancy outcomes of BOT patients.…”
Section: Discussionsupporting
confidence: 87%
“…There was no significant difference in PFS between the other methods of fertility-preserving surgery (USO and USO + CC) and radical surgery, or among the three styles of fertility-preserving surgery. This is corroborated by findings in other studies: Chen et al found that the choice of surgical methods used to preserve fertility had significant impact on recurrence and subsequent pregnancy [15]; the same is reported in other studies [16, 17]. Taken together, these results suggest that the types of fertility-preserving surgery have different impacts on oncologic and pregnancy outcomes of BOT patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, the difference in pregnancy rate among different fertility sparing surgery modalities was not statistically significant, which was in accordance with the results from previous studies. Compared with unilateral salpingo-oophorectomy, patients undergoing cystectomy had a higher pregnancy rate since more normal ovarian tissues were retained [ 27 ]. On the other hand, cystectomy may also increase the risk of recurrence and impact the DFS.…”
Section: Discussionmentioning
confidence: 99%
“…11 The re-ported rate of pregnancy in BOTs treated with conservative surgery varies between 32 and 65%. 12 In conclusion, it is important to make a detailed examination of ovarian cysts to ensure that any potential malignancy is not overlooked in young patients who wish to retain their fertility.…”
Section: Discussionmentioning
confidence: 99%